Audiovisual Aids using Flipped Classroom to Improve English Speaking Fluency in Sophomore Students at César Antonio Mosquera High School from 2021 to 2022 - Tatamues Chamorro, Angie Mariuxi (2022)
To propose Flipped classroom strategies using audio-visual aids to develop English speaking fluency in sophomore students at “César Antonio Mosquera” high school from 2021 to 2022.